Island of the sequined love nun ebook - Moore, Christopher (2009)
Take a wonderfully crazed excursion into the demented heart of a tropical paradise—a world of cargo cults, cannibals, mad scientists, ninjas, and talking fruit bats. Our bumbling hero is Tucker Case, a hopeless geek trapped in a cool guy's body, who makes a living as a pilot for the Mary Jean Cosmetics Corporation. But when he demolishes his boss's pink plane during a drunken airborne liaison, Tuck must run for his life from Mary Jean's goons. Now there's only one employment opportunity left for him: piloting shady secret missions for an unscrupulous medical missionary and a sexy blond high priestess on the remotest of Micronesian hells. Here is a brazen, ingenious, irreverent, and wickedly funny novel from a modern master of the outrageous.